Management of Rottboellia cochinchinensis and other weeds through sequential application of herbicides in dry direct-seeded rice in the Philippines. (December 2015) - Chauhan, Bhagirath Singh; Bajwa, Ali Ahsan
Abstract: Dry direct-seeded rice (DSR) systems are becoming popular due to resource conservation and economic returns but high weed pressure limits rice productivity. Rottboellia cochinchinensis (Lour.) W. D. Clayton is an emerging noxious weed of DSR and requires a suitable herbicide package for effective control. A field study was conducted to evaluate the efficacy of two pre-emergence (oxadiazon and pendimethalin) and two post-emergence (cyhalofop and bentazon) herbicides used in various combinations and sequences during two consecutive seasons (dry season, 2013–14 and wet season, 2014) at the International Rice Research Institute (IRRI), Los Baños, Philippines. Experiments were laid out in a randomised complete block design with three replications. Weedy plots were kept as control. All the herbicide treatments significantly reduced density and biomass of R. cochinchinensis and other dominating weeds at the flowering stage of rice during both seasons. The best treatment was pendimethalin followed by bentazon + cyhalofop, which caused 88–91% reductions in R. cochinchinensis density over the weedy control (9.4–13.0 plants m −2 ) during both seasons. It also reduced R. cochinchinensis biomass by 98–99% over the weedy control (331–344 g m −2 ). Different herbicide sequential treatments also controlled density and biomass of Cyperus rotundus L., Eclipta prostrata L., Echinochloa colona (L.) Link, and Murdannia nudiflora (L.) Brenan over the weedy control. Highest reductions in total weed density (82–84%) and total weed biomass (95–97%) over the weedy control were observed from pendimethalin followed by bentazon + cyhalofop applications during both seasons. All the herbicide treatments increased rice grain yield significantly over the control. The maximum grain yield was obtained from pendimethalin followed by bentazon + cyhalofop applications, which was 4.7 and 3.0 t ha −1 during the dry season, 2013–14 and the wet season, 2014, respectively. The results suggest that the pre-emergence application of pendimethalin followed by the combination of post-emergence herbicides (bentazon and cyhalofop) may control R. cochinchinensis and other noxious weeds in DSR effectively with subsequent increment in rice grain yield. Highlights: Rottboellia cochinchinensis is an emerging noxious weed in direct-seeded rice. Pendimethalin application followed by bentazon plus cyhalofop offered best weed control. Sequential herbicide application control weeds and improve rice yield.